Control and Anticipation of Social Interruptions: Reduced Stress and Improved Task Performance. - Carton, Andrew M.; Aiello, John R. (Journal of Applied Social Psychology, 2009)
Social interruptions are frequent occurrences that often have distressing consequences for employees, yet little research has gauged their effect on individuals. Participants were exposed to 2 social interruptions as they engaged in a computer task with an accepted performance goal. Participants who were able to anticipate social interruptions performed significantly better than did those who could not anticipate them. Participants who had the opportunity to prevent interruptions reported significantly less stress than those who did not have this opportunity. This reduction in stress resulted even when participants did not take advantage of this opportunity. Implications for job performance and job satisfaction are discussed. Organizational strategies for how leaders can help employees manage social interruptions are suggested. Reprinted by permission of the publisher.